Gut Microbiota and a Selectively Bred Taste Phenotype: A Novel Model of Microbiome-Behavior Relationships. Issue 5 (June 2016) - Lyte, Mark; Fodor, Anthony A.; Chapman, Clinton D.; Martin, Gary G.; Perez-Chanona, Ernesto; Jobin, Christian; Dess, Nancy K.
ABSTRACT: Objectives: The microbiota-gut-brain axis is increasingly implicated in obesity, anxiety, stress, and other health-related processes. Researchers have proposed that gut microbiota may influence dietary habits, and pathways through the microbiota-gut-brain axis make such a relationship feasible; however, few data bear on the hypothesis. As a first step in the development of a model system, the gut microbiome was examined in rat lines selectively outbred on a taste phenotype with biobehavioral profiles that have diverged with respect to energy regulation, anxiety, and stress. Methods: Occidental low and high-saccharin–consuming rats were assessed for body mass and chow, water, and saccharin intake; littermate controls had shared cages with rats in the experimental group but were not assessed. Cecum and colon microbial communities were profiled using Illumina 16S rRNA sequencing and multivariate analysis of microbial diversity and composition. Results: The saccharin phenotype was confirmed (low-saccharin–consuming rats, 0.7Δ% [0.9Δ%]; high-saccharin–consuming rats, 28.1Δ% [3.6Δ%]). Regardless of saccharin exposure, gut microbiota differed between lines in terms of overall community similarity and taxa at lower phylogenetic levels. Specifically, 16 genera in three phyla distinguished the lines at a 10% false discovery rate. Discussion: The study demonstrates for the first time that rodent lines created through selective pressure on taste and differing on functionally related correlates host different microbial communities. Whether the microbiota are causally related to the taste phenotype or its correlates remains to be determined. These findings encourage further inquiry on the relationship of the microbiome to taste, dietary habits, emotion, and health.